2018
DOI: 10.3310/hta22210
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management education for adults with poorly controlled epILEpsy [SMILE (UK)]: a randomised controlled trial

Abstract: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in ; Vol. 22, No. 21. See the NIHR Journals Library website for further project information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 167 publications
0
29
0
Order By: Relevance
“…Purposive recruitment methods were used. The first author (AM) invited by mail 47 PWE from a previous randomised controlled trial [ 33 ] who agreed to be contacted about future research. Fifteen PWE responded to the invitation and were screened; eight of whom were eligible to participate.…”
Section: Methodsmentioning
confidence: 99%
“…Purposive recruitment methods were used. The first author (AM) invited by mail 47 PWE from a previous randomised controlled trial [ 33 ] who agreed to be contacted about future research. Fifteen PWE responded to the invitation and were screened; eight of whom were eligible to participate.…”
Section: Methodsmentioning
confidence: 99%
“…The Modular Service Package Epilepsy study (MOSES) reported significant improvements in ASM tolerability, epilepsy knowledge, coping with epilepsy, and seizure frequency after 6 months following a 2-day SM education program [11]. Self-management education for people with poorly controlled epilepsy [SMILE (UK)] adapted MOSES for use in the United Kingdom and did not find the 2-day course to be effective in improving QOL or secondary outcome measures (anxiety and depression), after 12 months [12]. Though both MOSES and SMILE were randomized control trials (RCTs), MOSES included all adults with epilepsy whereas SMILE included only adults with chronic epilepsy who had two or more seizures in the prior 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…In developed countries, the incidence rate ranges from 24 to 53 per 100,000 person-years. [12] Antiepileptic drugs (AEDs) can prevent seizures in approximately 70% of adult patients with epilepsy. [3] However, AEDs nonadherence is highly prevalent, with estimates ranging from 20% to 80%.…”
Section: Introductionmentioning
confidence: 99%